Targeting cancer stem cells and signaling pathways by phytochemicals: Novel approach for breast cancer therapy. (October 2016) - Dandawate, Prasad R.; Subramaniam, Dharmalingam; Jensen, Roy A.; Anant, Shrikant
Abstract: Breast cancer is the most common form of cancer diagnosed in women worldwide and the second leading cause of cancer-related deaths in the USA. Despite the development of newer diagnostic methods, selective as well as targeted chemotherapies and their combinations, surgery, hormonal therapy, radiotherapy, breast cancer recurrence, metastasis and drug resistance are still the major problems for breast cancer. Emerging evidence suggest the existence of cancer stem cells (CSCs), a population of cells with the capacity to self-renew, differentiate and be capable of initiating and sustaining tumor growth. In addition, CSCs are believed to be responsible for cancer recurrence, anticancer drug resistance, and metastasis. Hence, compounds targeting breast CSCs may be better therapeutic agents for treating breast cancer and control recurrence and metastasis. Naturally occurring compounds, mainly phytochemicals have gained immense attention in recent times because of their wide safety profile, ability to target heterogeneous populations of cancer cells as well as CSCs, and their key signaling pathways. Therefore, in the present review article, we summarize our current understanding of breast CSCs and their signaling pathways, and the phytochemicals that affect these cells including curcumin, resveratrol, tea polyphenols (epigallocatechin-3-gallate, epigallocatechin), sulforaphane, genistein, indole-3-carbinol, 3, 3′-di-indolylmethane, vitamin E, retinoic acid, quercetin, parthenolide, triptolide, 6-shogaol, pterostilbene, isoliquiritigenin, celastrol, and koenimbin. These phytochemicals may serve as novel therapeutic agents for breast cancer treatment and future leads for drug development.